PROSEDUR STANDAR PELAKSANAAN WISATA ARUNG JERAM BANYUWANGI - Oktawirani, Panca; Akbar, Abim (Jurnal IKEOR, 2023)
Indonesia is blessed with vast natural resources. One of these resources is its rivers, which provide opportunities for tourist activities such as the popular water tourism of rafting. Pinus Camp 2 Songgon Banyuwangi is a famous tourist destination that utilizes the rapids of the Badeng River for rafting. Given the high risk associated with such activities, additional safety measures are imperative. The expectation is that standardized operating procedures will improve the safety of both tourists and rafting service providers in the water tourism industry. Qualitative data collection techniques including interviews, documentation and observation will be used to conduct this research. Based on the results of the data analysis, it has been determined that the rafting tourism business at Pinus Camp 2 Songgon Banyuwangi utilizes standard procedures at a rate of 77%, which meets the organizational standards outlined in the Regulation of the Minister of Tourism and Creative Economy of the Republic of Indonesia Number 13 of 2014 on Rafting Tourism Business Standards. To ensure continued compliance with these standards, management needs to review the Standard Operating Procedures (SOP) for rafting tourism.